Penguatan Literasi Numerasi dan Teknologi di SDN 21 Bathin Solapan Melalui Program Kampus Mengajar Angkatan 3: Pelaksanaan Program Kampus Mengajar di SDN 21 Bathin Solapan - Sinaga, Yessica Indah; Pakpahan, Carolina; Pardede, Surya Darma (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
This article reviews the process of improving learning in the Literacy, Numeration and Technology sections carried out at SDN 21 Bathin Solapan through the Campus Teaching Program Batch 3. The purpose of this program is because there are still many schools in Indonesia that face difficulties to overcome this, so The Ministry of Education and Culture created the Teaching Campus program which is part of the Merdeka Campus Program which was created for students to revive education in Indonesia. The improvement of learning carried out by the Teaching Campus students at SDN 21 Bathin Solapan is to create work programs that are able to arouse and also help the difficulties faced by students, and also to create learning programs in the field of technology that are able to increase their knowledge of technology, perform reading activities in the morning before starting the learning process to improve literacy skills and also create learning programs to hone numeracy skills. Other activities were also carried out to increase students' interest in learning at SDN 21 Bathin Solapan both in the field of science and in the extracurricular activities of the school. In addition to teaching and also doing activities with students, we also help with the school administration process, in order to alleviate and also correct errors in school administration and teachers. From the results of the activities that we have carried out through the Teaching Campus program, many changes have occurred to the students and the schools we are assigned to. Therefore, the Campus Teaching program is very useful to help alleviate and improve education in schools in Indonesia.